Child development accounts (CDAs): An asset-building strategy to empower girls in Uganda - Curley, Jami (Int Soc Work, 2014)
This study explores an innovative intervention for orphaned children in Uganda. It combines standard health care with an economic empowerment component. We refer to this combination as a family asset-based intervention, which provides each child with a child development account (CDA), a matched savings account for secondary schooling; financial education; and a mentor. This article examines the educational outcomes of the girls in this study. The results from the first two waves of the study indicate that CDAs have the potential to begin to help negate the effects of past gender inequalities and to help provide a path for young girls to move forward.